2010
DOI: 10.1021/am100757g
|View full text |Cite
|
Sign up to set email alerts
|

Electrowetting on Paper for Electronic Paper Display

Abstract: The use of paper as a material for various device applications (such as microfluidics and energy storage) is very attractive given its flexibility, versatility, and low cost. Here we demonstrate that electrowetting (EW) devices can be readily fabricated on paper substrates. Several categories of paper have been investigated for this purpose, with the surface coating, roughness, thickness, and water uptake, among the most important properties. The critical parameter for EW devices is the water contact angle (CA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
85
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 132 publications
(87 citation statements)
references
References 32 publications
1
85
0
Order By: Relevance
“…[206][207][208][209] However, the high requirements on the drive transistors, the required sealing, and the typically rather expensive fabrication processes of luminescent displays make the use of low-cost paper substrates questionable.…”
Section: Displaysmentioning
confidence: 99%
“…[206][207][208][209] However, the high requirements on the drive transistors, the required sealing, and the typically rather expensive fabrication processes of luminescent displays make the use of low-cost paper substrates questionable.…”
Section: Displaysmentioning
confidence: 99%
“…It has already been demonstrated that biodegradable substrates such as cellulose may be used both as substrates for LEDs, displays, and thin-fi lm transistors. [40][41][42] A recent study shows the usage of cellulosebased dielectrics in high-performance organic complementary inverters. [ 43 ] Additionally, FF-MNS, which is almost fully biodegradable, has also been demonstrated as a dielectric layer in top-and bottom-gate organic FETs.…”
Section: Biodegradabilitymentioning
confidence: 99%
“…The only existing biodegradable polymer with an all-carbon backbone is polyvinyl alcohol (PVA). The main substrate type that has successfully been integrated in organic electronic technology in recent years is cellulose in its various modifications [10][11][12][13]. Although the initial roughness of these substrate types is initially challenging, the roughness level could be lowered either by adjusted fabrication parameters or by additional (bio)coatings.…”
Section: Substrate Materialsmentioning
confidence: 99%